2013
DOI: 10.1021/cm3041345
|View full text |Cite
|
Sign up to set email alerts
|

Water Oxidation Catalysis by Nanoparticulate Manganese Oxide Thin Films: Probing the Effect of the Manganese Precursors

Abstract: Nanoparticulate manganese oxides, formed in Nafion polymer from a series of molecular manganese complexes of varying nuclearity and metal oxidation state, are shown to effectively catalyze water oxidation under neutral pH conditions with the onset of electrocatalysis occurring at an overpotential of only 150 mV. Although XAS experiments indicate that each complex generates the same material in Nafion, the catalytic activity varied substantially with the manganese precursor and did not correlate with the amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 90 publications
6
109
0
Order By: Relevance
“…Mn oxides show good activities [6][7][8][9][10][11][12][13], are abundant and low cost. They occur, though, in a wide number of structures and oxidation states, so constituting a wide field.…”
Section: Introductionmentioning
confidence: 99%
“…Mn oxides show good activities [6][7][8][9][10][11][12][13], are abundant and low cost. They occur, though, in a wide number of structures and oxidation states, so constituting a wide field.…”
Section: Introductionmentioning
confidence: 99%
“…With the comprehensive characterization of Co-POM under various reaction conditions, it is suggested that Co-POM serves as the true WOC in chemical catalysis, whereas it transforms to active cobalt oxide nanoparticles in electrochemical oxidation [28,40,103,104]. As the selected element by nature, molecular manganese catalysts are surprisingly rare and easily decompose to Mn oxide in both chemical and electrochemical catalysis [21,86,87]. For iron-based catalysts, the true active species strongly depend on the catalytic conditions such as pH.…”
Section: Discussionmentioning
confidence: 99%
“…The extremely high resolution of TEM enables the detection of fine structural details, even as small as a few nanometers in size. TEM is widely used for elemental analysis and nanoparticle detection of the deposited films, but not for solution samples [21,22].…”
Section: Homogeneous or Heterogeneous: How To Identify The Real Wocsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mn oxides were reported as water-oxidizing catalysts for artificial photosynthetic systems [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Among Mn oxides, nanolayered Mn oxides with different organic or inorganic ions between layers are efficient and stable in water oxidation [41].…”
Section: Introductionmentioning
confidence: 99%